Profiling the Australian high performance & sports science workforce - Dawson, A.; Wehner, K.; Gastin, P.; Dwyer, D.; Kremer, P.; Allan, M. (Deakin University, Cenre for Exercise and Sports Scienece, 2011)
Australia is viewed as leader in the field of sports science, with Australian sports scientists highly sought after and respected worldwide (1). However, despite the important contribution of sports scientists to the development of professional sport in Australia (1-3), we know little about these sport professionals who play an important role in the development and success of athletes, teams and sport organisations. This report provides a more formal understanding of the high performance and sports science workforce with the purpose of informing the policy development of Australia`s sport governing bodies and education providers to inform sport management practices that will enhance the support and development of current and future high performance managers and sports scientists. The data presented in this report provides valuable insight about the scope of the profession to enable further development of strategic plans for the industry.